Kejadian Ikutan Paska Vaksinasi COVID-19: Refleksi dan Pembelajaran Setelah Pandemi - Mailoor, Wulan Dea Debora; Purnawinadi, I Gede (NUTRIX, 2024)
COVID-19 vaccine is a weakened antigen as well as the government's efforts to reduce COVID-19 cases, this is not far from the term post-vaccination adverse events (KIPI) which can occur after vaccination or immunization as a response of the body. The purpose of the study was to determine the relationship between the COVID-19 vaccine and post-vaccination adverse events in nursing students at Klabat University. Quantitative research method with a cross-sectional approach and data collection using questionnaires. The results of the study found that the majority experienced local KIPI with the type of KIPI pain in the injection area 115 (29.7%) respondents at the first and second doses. The results of the study found that the majority experienced systemic KIPI with the type of KIPI feeling unwell 101 (26.1%), KIPI muscle pain 102 (26.4%), and KIPI drowsiness 112 (28.9%) respondents. The results of the local KIPI chi-square test showed a p-value <0.05, namely there was a significant relationship between the COVID-19 vaccine and KIPI pain, redness, and swelling of the injection area. The results of the chi-square test for systemic AEFI fever, headache, dizziness, malaise, muscle pain, fatigue, chills, drowsiness, and changes in appetite showed a p-value <0.05, which means there is a significant relationship, while for systemic AEFI nausea/vomiting, there is no significant relationship from the chi-square test with a p-value> 0.05. Further research recommendations add the status of booster vaccination two, age factors, gender, type of AEFI diarrhea, cough, and runny nose, excessive sweating, rash, and itching. Vaksin COVID-19 adalah antingen yang dilemahkan sekaligus upaya pemerintah dalam mengurangi kasus COVID-19, hal ini tidak jauh dari kata kejadian ikutan paska vaksinasi (KIPI) yang bisa terjadi setelah vaksinasi atau imunisai sebagai respon tubuh. Tujuan penelitian untuk mengetahui hubungan vaksin COVID-19 dan kejadian ikutan paska vaksinasi pada mahasiswa keperawatan Universitas Klabat. Metode penelitian kuantitatif dengan pendekatan cross-sectional serta pengumpulan data menggunakan kuesioner. Hasil penelitian didapati mayoritas mengalami KIPI lokal dengan jenis KIPI nyeri area suntikan 115 (29,7%) responden pada dosis pertama dan kedua. Hasil penelitian didapati mayoritas mengalami KIPI sistemik dengan jenis KIPI tidak enak badan 101 (26,1%), KIPI nyeri otot 102 (26,4%) dan KIPI mengantuk 112 (28,9%) responden. Hasil uji chi-square KIPI lokal menunjukkan p-value <0,05 yaitu terdapat hubungan yang signifikan antara vaksin COVID-19 dengan KIPI nyeri, kemerahan dan bengkak area suntikan. Hasil uji chi-square KIPI sistemik demam, sakit kepala, pusing, tidak enak badan, nyeri otot, kelelahan, menggigil, mengantuk dan perubahan napsu makan menunjukkan p-value <0,05 yaitu terdapat hubungan yang signifikan, sedangkan untuk KIPI sistemik mual/muntah tidak terdapat hubungan yang signifikan dari uji chi-square dengan p-value >0,05. Rekomendasi penelitian selanjutnya menambahkan status vaksinasi booster dua, faktor usia, jenis kelamin, jenis KIPI diare, batuk pilek, keringat berlebih, ruam, dan gatal-gatal.